2012
DOI: 10.3109/00016489.2012.680494
|View full text |Cite
|
Sign up to set email alerts
|

Platinum concentration in sentinel lymph nodes after preoperative intra-arterial cisplatin chemotherapy targeting primary tongue cancer

Abstract: Conclusion.We concluded that intra-arterially injected cisplatin passed via lymph flow into sentinel nodes (SNs) as the platinum concentration in the SNs was higher than that in the non-sentinel nodes (NSNs). It is possible that pre-operative intra-arterial chemotherapy targeting primary cancer also has a therapeutic effect on subclinical metastatic SNs.Objectives. Intra-arterial chemoradiotherapy has been reported to be effective against not only primary tumors but also nodal metastases. We considered the hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 19 publications
(25 reference statements)
1
1
0
Order By: Relevance
“…The reason for the low recurrence rate in our study is speculated to be that intra-arterially injected cisplatin targeting the primary tumor has a beneficial effect on subclinical metastatic lymph nodes. It has been reported that intra-arterially injected cisplatin can pass, via lymph flow, into the lymph nodes in patients with tongue cancer [8][9]. These reports appear to support our hypothesis.…”
Section: Discussionsupporting
confidence: 89%
“…The reason for the low recurrence rate in our study is speculated to be that intra-arterially injected cisplatin targeting the primary tumor has a beneficial effect on subclinical metastatic lymph nodes. It has been reported that intra-arterially injected cisplatin can pass, via lymph flow, into the lymph nodes in patients with tongue cancer [8][9]. These reports appear to support our hypothesis.…”
Section: Discussionsupporting
confidence: 89%
“…20 Some reports have also suggested that superselective IACRT has a beneficial effect on cervical lymph node metastasis 10,21 and achieves significantly higher platinum levels in sentinel lymph nodes when the IACRT is cisplatin-based. 22 The markedly favorable histologic response seen in the authors' study likely reflects the synergistic effect of cisplatin-based intra-arterial chemotherapy spreading from the primary lesion to cervical lymph node metastases and the combination of RT with S-1. The effect on OSCC was detectable after only 1 or 2 infusions of intra-arterial chemotherapy combined with the minimum dose of RT (40 Gy).…”
Section: Discussionmentioning
confidence: 73%